2022
DOI: 10.3390/molecules27165351
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Electrospun Polycaprolactone—Propolis Mats Composed of Different Morphologies for Potential Use in Wound Healing

Abstract: This study aimed to investigate different types of morphologies obtained using the electrospinning process to produce a material that enables wound healing while performing a controlled release. Using benign solvents, the authors prepared and characterised electrospun polycaprolactone mats loaded with propolis, a popular extract in traditional medicine with potential for skin repair. Different morphologies were obtained from distinct storage periods of the solution before electrospinning to investigate the eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 86 publications
4
19
0
Order By: Relevance
“…%) in relation to that of the pure PCL solution, which may be related to a lubricant behavior of the molecules of the extract inside the polymeric network. This behavior was also observed in the results presented by Figueiredo et al (2022) [54], who observed the lubricant behavior on viscosity when incorporating propolis extract into the PCL solution.…”
Section: Viscosity Evaluationsupporting
confidence: 82%
See 4 more Smart Citations
“…%) in relation to that of the pure PCL solution, which may be related to a lubricant behavior of the molecules of the extract inside the polymeric network. This behavior was also observed in the results presented by Figueiredo et al (2022) [54], who observed the lubricant behavior on viscosity when incorporating propolis extract into the PCL solution.…”
Section: Viscosity Evaluationsupporting
confidence: 82%
“…For the second heating cycle, Figure 7(b), the PCL electrospun mats with the P. major extract showed a decrease of approximately 36.6 % in the degree of crystallinity of the fibers with 5.3 wt.% of the extract compared with PCL fibers without the extract (PCL_00) (Table 2). This demonstrates an interaction between freeze-dried extract and PCL chains that can be attributed to the fact that the P. major molecules were able to allocate themselves between polymer chains, promoting the increase in the space between them, and increase in the difficulty of these chains in reorganizing as ordered crystal structures [54,67]. Nevertheless, this large decrease in the degree of crystallinity was not observed when the concentration of the extract was increased to 10.6 wt.% (PCL_10.6), and a slight increase in crystallinity was observed with relation to PCL_5.3.…”
Section: Thermal Behavior Of Electrospun Matsmentioning
confidence: 93%
See 3 more Smart Citations